2010
DOI: 10.1002/cbdv.200900308
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Affects the Conformation of Apo Form, not Holo Form, of BRCA1 RING Finger Domain and Confers Thermal Stability

Abstract: The breast cancer suppressor protein 1 (BRCA1) has been shown to participate in genomic integrity maintenance. Preclinical and clinical studies have recently revealed that the inactivation of BRCA1 in cancer cells leads to chemosensitivity. Approaching the BRCA1 RING protein as a potentially molecular target for a platinum-based drug might be of interest in cancer therapy. In the present study, the in vitro platination of the BRCA1 RING protein by the anticancer drug cisplatin was observed. The protein contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The BRCA1 RING domain has been found to form favourable intramolecular and intermolecular cross-links caused by cisplatin (Atipairin et al, 2010). Although cisplatin has been demonstrated to induce protein dimerization and has caused perturbations in some protein structures, the secondary structure of the BRCA1 RING domain in the apo-form was maintained and underwent more folded structural rearrangement after increasing cisplatin concentrations as judged by an increase in the negative CD spectra at 208 and 220 nm.…”
Section: Cisplatin Binding To the Brca1 Ring Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…The BRCA1 RING domain has been found to form favourable intramolecular and intermolecular cross-links caused by cisplatin (Atipairin et al, 2010). Although cisplatin has been demonstrated to induce protein dimerization and has caused perturbations in some protein structures, the secondary structure of the BRCA1 RING domain in the apo-form was maintained and underwent more folded structural rearrangement after increasing cisplatin concentrations as judged by an increase in the negative CD spectra at 208 and 220 nm.…”
Section: Cisplatin Binding To the Brca1 Ring Domainmentioning
confidence: 99%
“…In order to locate the binding site of cisplatin on the BRCA1 (1-139) protein, in-gel tryptic digestion of the free BRCA1 and the cisplatin-BRCA1 adducts (molar ratio 1:1) were subjected to analysis by LC-MS. A unique fragment ion of 656.29 2+ was obtained from the cisplatin-BRCA1 adduct digests. Tandem mass spectrometric analyses of this fragment ion indicated that the ion arose from (Atipairin et al, 2010).…”
Section: Cisplatin Binding To the Brca1 Ring Domainmentioning
confidence: 99%
See 3 more Smart Citations